Neuraxial Anesthesia in the Geriatric Patient - Sivevski, Atanas G.; Karadjova, Dafina; Ivanov, Emilija; Kartalov, Andrijan (Frontiers in Medicine, 2018)
Neuraxial anesthesia remains a well-accepted option to minimize the perioperative side effects in the geriatric patients. Results from the current research have shifted the focus from the conventional approach to spinal anaesthesia to the concept of low dose local anesthetic combined with lipophilic opioids. What remains clear from all these studies is that hemodynamic stability is much better in patients who received low-doses of intrathecal bupivacaine in combination with opioids, which is possibly result of a potent synergistic nociceptive analgesic effect and their minimal potential effects on sympathetic pathways thus minimizing spinal hypotension. Spinal anesthesia with 5-7,5 mg of 0,5% heavy bupivacaine, fentanyl 20 mcg and morphine 100 mcg added to the perioperative plan decreased the incidence of spinal hypotension and improved perioperative outcomes in the geriatric patients undergoing - low segment gynecological surgical procedures.